2011
DOI: 10.1536/ihj.52.7
|View full text |Cite
|
Sign up to set email alerts
|

Role of Preoperative Atorvastatin Administration in Protection Against Postoperative Atrial Fibrillation Following Conventional Coronary Artery Bypass Grafting

Abstract: SummaryAtrial fibrillation (AF) is one of the most common postoperative arrhythmias in patients who undergo coronary artery bypass grafting (CABG). The aim of this study was to evaluate the effect of preoperative atorvastatin on postoperative atrial fibrillation following coronary artery bypass grafting with cardiopulmonary bypass (CCABG). One hundred consecutive patients undergoing elective CCABG, without history of AF or previous statin treatment, were enrolled and randomly assigned to a statin group (atorva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
64
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 19 publications
1
64
2
2
Order By: Relevance
“…However, these recommendations are based on randomized trials that were small and had other important limitations. An updated meta-analysis of the results from previously published randomized trials of perioperative statin therapy (15)(16)(17)(18) showed an approximate halving of the incidence of postoperative AF with statins as compared with placebo. However, those trials involved small numbers of patients and had other important limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these recommendations are based on randomized trials that were small and had other important limitations. An updated meta-analysis of the results from previously published randomized trials of perioperative statin therapy (15)(16)(17)(18) showed an approximate halving of the incidence of postoperative AF with statins as compared with placebo. However, those trials involved small numbers of patients and had other important limitations.…”
Section: Discussionmentioning
confidence: 99%
“…However, those trials involved small numbers of patients and had other important limitations. For example, only same of the trials were designed with a prespecified postoperative AF as an outcome (16,29,30), and only one trial (29) included an intention-to-treat analysis of the effect on AF as detected in a systematic and blinded manner. Furthermore, a recent systematic Cochrane review of those trials showed evidence of selective reporting and publication bias (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atrial fibrillation (AF) is one of the most common postoperative arrhythmias in patients who undergo coronary artery bypass grafting (1). This complication leads to increases in mortality and morbidity rate in coronary bypass surgery and in hospital stay caused by excess usage of medications (2).…”
mentioning
confidence: 99%
“…Açık cerrahi yöntem ile karşılaştırıldığında endovasküler yöntemin üstünlükleri, preoperatif kan kaybının az olması, çoğu zaman epidural anestezi altında uygulanabilmesi, hastanede kalış süresinin kısa olması ve daha düşük mortalite ve morbidite ile seyretmesi olarak sıralanabilir (1,2). Özellikle, yüksek risk taşıyan hastalarda, düşük mortalite ve morbidite ile seyrettiği gözlenmektedir (3).…”
unclassified